Peranan Lembaga Adat dan Kearifan Lokal dalam Upaya Pencegahan dan Penyelesaian Konflik Horizontal di Provinsi Jambi - Donny Michael (Jurnal HAM, 2012)
Conflict between people or between groups of people is a situation that shall always exist in every social interaction. Customary institutions (Lembaga Adat) and local knowledge as part of the structure of a society play a role in influencing conflict attitude and behavior, which may potentially amount to violence. The existence of customary institutions and local knowledge has become one of the community robustness pillars that are expected to overcome any social problems, or to switch people's violent behavior into a positive one without injuring others or the community at large. The role of traditional institutions, based on the functioning of the community in general, is as a common body whenever a situation requires a traditional affirmative action in the society. Traditional institution, as a component of society, is thus essential for the integrity of the structure of society itself, without which a community could lose its identity as a civilized society along with local wisdom within.